Analisis Pemanfaatan Website X-Reading di SMA Alfa Centauri - Adinda Khoerunnisa Aprilia; Ardiansah (Jurnal IPI (Ikatan Pustakawan Indonesia), 2023)
Schools in Indonesia have begun to instill the importance of literacy to the school community. The School Literacy Movement is one of the programs held in almost every school in Indonesia. At SMA Alfa Centauri using a paid website called X-Reading. X-Reading was only used at Alfa Centauri High School in the middle of the school year. The purpose of this research is to find out how to use X-Reading and how to use X-Reading. The method used in this study is a qualitative descriptive method with the type of observational research analyzed based on two main variables in TAM theory, namely perceptions of ease of use and usefulness of use. The use of X-Reading at SMA Alfa Centauri is used as a GLS and as a facility for students to improve their English skills. With a clear and easy to understand display and many useful features, it can make it easier for students and teachers to use X-Reading. The many benefits obtained by using X-Reading are making it easier to read books, improving English skills, making it easier for teachers to give English assignments, as LMS, and as additional recreation for students. Obstacles as additional recreation for students.